Hierarchical Zn‐Doped CoO Nanoflowers for Electrocatalytic Oxygen Evolution Reaction. Issue 5 (5th February 2019) - Huo, Meiling; Yang, Zhiyuan; Yang, Chenxi; Gao, Zhong; Qi, Jing; Liang, Zuozhong; Liu, Kaiqiang; Chen, Heyin; Zheng, Haoquan; Cao, Rui
Abstract: Hierarchical Zn‐doped CoO nanoflowers have been prepared using their hydroxides as precursors. The nanoflowers are assembled by dozens of 2D nanoplates. Each nanoplate is formed by numerous Zn‐doped CoO nanoparticles. Zn‐doped CoO catalyst is highly efficient for electrocatalytic water oxidation with a low overpotential ( η =293 mV at j =10 mA cm −2 ) and long‐term stability, which is comparable to the commercial RuO2 catalysts in alkaline media. The 3D hierarchical structure provides abundant surface catalytic sites, while the density functional theory (DFT) calculations show that the Zn doping is also beneficial for the enhanced oxygen evolution reaction (OER) activities. This series of novel hierarchical porous nanoflowers is a promising anode material for water oxidation. Abstract : Spring (nano)flowers . The 3D hierarchical structure of the Zn‐doped CoO provides abundant surface catalytic sites and is beneficial for the efficient mass diffusion during catalysis. Zn‐doped CoO catalyst is highly efficient for electrocatalytic water oxidation with a low overpotential ( η =293 mV at j =10 mA cm −2 ) and long‐term stability, which is comparable to the commercial RuO2 catalysts in alkaline media.